Prevalence of musculoskeletal pain in cyclists: a systemic review (Research, Society and Development, 2021)
Cycling is one of the most popular activities around the world and despite being considered a modality of low impact, some studies indicate that an inadequate posture or lack of preparation of athletes for this practice lead to musculoskeletal injuries and pain. In this sense, the objective was to verify, from a systematic literature review, the prevalence of musculoskeletal pain in cycling practitioners based on studies found in online databases, published in the last ten years. It is an exploratory, qualitative study, of the systematic review type. For data collection, the Proknow-C methodology was used and for the analysis of the results, descriptive analysis was chosen. The results indicate a high prevalence of pain among cyclists, with pain in the lumbar spine, knees and upper and lower limbs being common. Emphasizing the importance of Physiotherapy in the treatment and prevention of painful symptoms that can be aggravated by the lack of specialized assistance and preventive exercises.